2020
DOI: 10.1123/jsr.2019-0339
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kinesio Tape on Factors for Neuromuscular Control of the Lower-Extremity: A Critically Appraised Topic

Abstract: Clinical Scenario: Joint instability is a common condition that often stems from inadequate muscle activation and results in precarious movement patterns. When clinicians attempt to mechanically treat the unstable joint rather than attending to the underlying cause of the instability, patient outcomes may suffer. The use of kinesiology tape (KT) on an unstable joint has been proposed to aid in improving lower-extremity neuromuscular control. Clinical Question: Does KT improve factors of neuromuscular control i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Conventional tapes and braces are thought to improve knee stability; however, they may limit the range of motion of the knee and decrease the knee flexion angle during the landing phase, increasing the risk of ACL injury [29]. The elasticity of KT allows achieving a partial to full range of motion and hence does not limit the range of motion of the joint [30]. Additionally, KT is thought to improve blood circulation, and this physiological change may affect the muscle and myofascial functions and increase the range of motion of the joint [31][32][33].…”
Section: Kinematicsmentioning
confidence: 99%
“…Conventional tapes and braces are thought to improve knee stability; however, they may limit the range of motion of the knee and decrease the knee flexion angle during the landing phase, increasing the risk of ACL injury [29]. The elasticity of KT allows achieving a partial to full range of motion and hence does not limit the range of motion of the joint [30]. Additionally, KT is thought to improve blood circulation, and this physiological change may affect the muscle and myofascial functions and increase the range of motion of the joint [31][32][33].…”
Section: Kinematicsmentioning
confidence: 99%
“…In this line, a recent study applied a KT bandage to the knee with a tension of 75%, achieving a significant reduction in the knee valgus during the Jump Landing Test in men [26]. To date, there is inconclusive evidence that KT improves neuromuscular control at the knee in symptomatic populations [27], and it would be interesting to analyze the effectiveness of KT in reducing knee valgus in several closed kinetic chain functional tests focusing on women, since they have a greater risk of suffering from ACL injuries.…”
Section: Introductionmentioning
confidence: 99%
“…KT application to college basketball players with FAI has recently been the focus of muscle strength and balance ability research, and the existing research on KT on muscle strength and balance ability is still controversial. The results of some studies indicate that KT does not seem to increase muscle strength or improve the balance ability of subjects ( Shields et al, 2013 ; Bailey and Firth, 2017 ; Martonick et al, 2020 ). However, other studies have shown that KT plays a certain role in improving the muscle strength and proprioception of injured people ( Williams S et al, 2012 ; Lin et al, 2021b ; Mao et al, 2021 ; Biz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%